Análise estatística de parâmetros de qualidade de águas superficiais como indicadores da geoquímica do selênio em uma mina de carvão canadense - Silva, Emiliano Mendonça (2012)
Although it is an essential element in the metabolism of animals, the adverse effects of elevated concentrations of selenium in the environment have been a parameter of concern in coal mining areas. Studies have been demonstrating that the presence of nitrate in anoxic environments can prevent selenium reduction as well as act as an electron acceptor capable of oxidizing sulfide and selenium minerals. In mine settings, nitrate as a residue from blasting materials could, therefore, contribute to the leaching of oxidized forms of Se(IV) and Se(VI) to water bodies downstream the mines, in a way Se could reach toxic levels to the aquatic biota. This work presents the results of Principal Component Analysis and Correlation Analysis undertaken on a database of hydrogeochemical parameters of surface water from Trend Mine, an open pit coal mine located in the Province of British Columbia, Canada. The objectives of this work were to understand the geochemical associations of selenium in the studied area, as well as the possible leaching and/or attenuating mechanisms of the element to the receiving water bodies downstream the mine. The results indicate that the main source of selenium to the mine sediment ponds is derived from the oxidation of sulfide minerals. Strong correlations between Se and NO3 - , as well as SO4 2- and NO3 - suggest that nitrate participates in the oxidation of sulfide/selenium minerals either by an excessive use of explosives in the mine, which would generate thinner fractions of waste rocks, more susceptible to oxidation; or by the action of nitrate in redox processes that would cause the oxidation of S and Se in anoxic settings. Elevated concentrations of hardness in water demonstrated to be inversely proportional to the correlations of Se and NO3 - and SO4 2- and NO3 - , possibly due to the co-precipitation of Se and SO4 2- with secondary minerals, such as calcite and gypsum. This would be an attenuating mechanism that could reduce the influence of NO3 - over Se and S, however, further studies need to be undertaken in order to assess the effectiveness of this mechanism in the attenuation of Se compounds in mine environments.